KEMAMPUAN MENGELOLA SUMBER DAYA PESISIR BERDASARKAN THE NEW ENVIRONMENTAL PARADIGM (Studi Korelasional pada masyarakat di Kabupaten Wakatobi Kecamatan Tomia)*) - Ihsyaluddin Ihsyaluddin (Program Studi Manajemen Lingkungan, 2013)
The objectives of this research are to obtain the differences of the new environmental paradigm (NEP) and the ability of coastal resources management on people live in Wakatobi Regency distric Tomia South Eart Sulawesi. This research applied survey method with 60 people as sample which seleated randomly. Regression and corelation analysis have been applied. Research finding reveal that there is a positive correlation between people NEP with people ability to manage coastal resources. There for its want to manage coastal resources effectively people NEP should be taking consideration